Pengaruh Model Pembelajaran Operant Conditioning terhadap Hasil Belajar Matematika Kelas V Kurikulum Merdeka Belajar - Siska Tresia Oktari; Yanti Fitria; Risda Amini (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The low mathematics learning outcomes of elementary school students is a problem in the implementation of the independent learning curriculum. The assumption of the difficulty of mathematics in students' thinking, the monotony of the learning process and the lack of teacher innovation and creativity are the main factors in the low learning outcomes. One interesting learning theory to apply in learning mathematics is operant conditioning learning theory, this theory focuses on changes in student behavior and is effective for application to children in elementary schools. This research uses a quantitative approach (Quantitative Approach). The research design was a pretest-posttest control group design. This research was conducted on fifth grade students at SD Negeri 20 Indarung which is located in the Lubuk Kilangan District, Padang City, West Sumatra. Data analysis techniques are in the form of descriptive analysis techniques consisting of prerequisite tests in the form of normality tests, homogeneity tests, and hypothesis testing using different tests or T-tests (T-Test). The results of this study indicate that there is a significant influence in the application of the operant conditioning model compared to the direct teaching model on the mathematics learning outcomes of fifth grade students at SD Negeri 20 Indarung Kota Padang (p<0.05). Keywords: Operant Conditioning, Learning Outcomes, Independent Learning Curriculum